Gender Differences in Plasma Ghrelin Levels in Hemodialysis Patients. Issue 1 (24th October 2018) - Sakao, Yukitoshi; Ohashi, Naro; Sugimoto, Mitsushige; Ichikawa, Hitomi; Sahara, Shu; Tsuji, Takayuki; Kato, Akihiko; Fujigaki, Yoshihide; Sugimoto, Ken; Furuta, Takahisa; Yasuda, Hideo
Abstract: Ghrelin is an orexigenic hormone mainly secreted by the stomach, and it decreases according to the severity of gastric atrophy. Ghrelin has multiple favorable functions, including protein anabolism enhancement, anti‐inflammatory activity, and cardiovascular protection, and is associated with survival in hemodialysis (HD) patients. Although the plasma level and role of ghrelin may be different depending on gender, they have not been completely assessed in HD patients. We enrolled 80 (male/female: 51/29) maintenance HD patients. An upper gastrointestinal endoscopic examination was performed for all patients to determine the severity of gastric mucosal atrophy and Helicobacter pylori infection. We measured plasma acyl and desacyl ghrelin levels and assessed the association between ghrelin levels and relevant clinical parameters, including nutrition, inflammation, atherosclerosis, and bone metabolism, by gender. Both acyl and desacyl ghrelin levels in female HD patients were significantly higher than those in male HD patients. When stratified by gastric mucosal atrophy, these gender differences were observed only in patients without gastric atrophy. In female patients, acyl ghrelin level was negatively correlated with age. In male patients, both acyl and desacyl ghrelin levels were positively correlated with bone mineral density. Multiple regression analysis showed significant positive correlations between both ghrelin levels and female gender after adjusting for confounding factors. Plasma ghrelin levels were higher in female HD patients than in male HD patients. The gender difference was more evident in patients without gastric atrophy.